Fields of Data: Exploring AI’s Impact on Modern Farming - Shreyas Sunil Ninghot; Sushil Bakhtar (International Journal of Solid State Innovations & Research, 2024)
The Food and Agriculture Organization (FAO) of the United Nations projects that by 2050, there will be a further 2 billion people on the planet, but just 4% of that additional land will be used for agriculture. Under such circumstances, the most recent technical developments and solutions to the farming industry’s obstacles can be used to achieve more effective farming methods. The direct implementation of machine intelligence or artificial intelligence in the farming industry may represent a paradigm shift in the way that farming is carried out today. This study offers a prospective viewpoint on the revolutionary possibilities of AI-driven agricultural solutions. Farmers may preserve or even improve crop quality while increasing output and efficiency by utilizing artificial intelligence. These technologies streamline several parts of agricultural production, from planting and cultivation to harvesting and distribution, enabling a faster go-to-market (GTM) strategy. They range from predictive analytics that project agricultural yields and market demand to precision farming methods that maximize the use of resources like water, fertilizer, and pesticides. AI can also help with disease identification and crop monitoring, enabling early intervention and better crop health. This includes innovations that can further decrease labor needs and boost efficiency, such robotic harvesting systems, and autonomous farming equipment. Using AI in agriculture has long been seen as one of the best ways to alleviate the shortage of food and adjust to the demands of an expanding population. An overview of AI’s use in agronomic fields and its advancements in lab research is given in this paper. The analysis begins by outlining two areas in which artificial intelligence (AI) has the potential to be highly influential: soil management and weed control. Next, the technology known as the Internet of Things (IoT), which has enormous promise for future applications, is discussed.
Keywords: Agriculture; Crop; FAO; Robotics; artificial intelligence; farming